Tuning gold-based surface functionalization for streptavidin detection: A combined simulative and experimental study - Dutta, Sutapa; Gagliardi, Mariacristina; Bellucci, Luca; Agostini, Matteo; Corni, Stefano; Cecchini, Marco; Brancolini, Giorgia (Frontiers in Molecular Biosciences, 2022)
A rationally designed gold functionalized surface capable of capturing a target protein is presented using the biotin-streptavidin pair as a proof-of-concept. We carry out multiscale simulations to shed light on the binding mechanism of streptavidin on four differently biotinylated surfaces. Brownian Dynamics simulations are used to reveal the preferred initial orientation of streptavidin over the surfaces, whereas classical molecular dynamics is used to refine the binding poses and to investigate the fundamental forces involved in binding, and the binding kinetics. We assess the binding events and the stability of the streptavidin attachment through a quartz crystal microbalance with dissipation monitoring (QCM-D). The sensing element comprises biotinylated polyethylene glycol chains grafted on the sensor gold surface via thiol-ene chemistry. Finally, we compare the results from experiments and simulations. We find that the confined biotin moieties can specifically capture streptavidin from the liquid phase, and provide guidelines on how to exploit the microscopic parameters obtained from simulations to guide the design of further biosensors with enhanced sensitivity.